The overlap method is a safe and feasible for esophagojejunostomy after laparoscopic-assisted total gastrectomy - Morimoto, Mamoru (World J Surg Oncol, 2014)
BACKGROUND: Laparoscopic procedures are increasingly being applied to gastric cancer surgery, including total gastrectomy for tumors located in the upper gastric body. Even for expert surgeons, esophagojejunostomy after laparoscopy-assisted total gastrectomy (LATG) can be technically challenging. We perform the overlap method of esophagojejunostomy after LATG for gastric cancer. However, technical questions remain. Is the overlap method safer and more useful than other anastomosis techniques, such as methods using a circular stapler? In addition, while we perform this overlap reconstruction after LATG in a deep and narrow operative field, can the overlap method be performed safely regardless of body habitus? This study aimed to evaluate these issues retrospectively and to review the literature. METHODS: From October 2005 to August 2013, we performed LATG with lymph-node dissection and Roux-en-Y reconstruction using the overlap method in 77 patients with gastric cancer. This study examined pre-, intra- and postoperative data. RESULTS: Mean operation time, time to perform anastomosis, and estimated blood loss were 391.4 min, 36.3 min, and 146.9 ml, respectively. There were no deaths, and morbidity rate was 13%, including one patient (1%) who developed anastomotic stenosis. Mean postoperative hospitalization was 13.4 days. Surgical outcomes did not differ significantly by body mass index. CONCLUSIONS: First, the overlap method for esophagojejunostomy after LATG is safe and useful. Second, this method can be performed irrespective of the body type of the patient. In particular, in a deep and narrow operative field, the overlap method is more versatile than other anastomosis methods. We believe that the overlap method can become a standard reconstruction technique for esophagojejunostomy after LATG.